Professional issues in information technology - Bott, Frank (British Computer Society, 2005)
This book explores the relationship between technological change, society and the law, and the powerful role that computers and computer professionals play in a technological society. It is designed to accompany the BCS Professional Examination Core Diploma Module: Professional Issues in Information Systems Practice.